2017
DOI: 10.1590/0001-3765201720170071
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of alginate and gelatin microcapsules containing Lactobacillus rhamnosus

Abstract: This paper describes the preparation and characterization of alginate beads coated with gelatin and containing Lactobacillus rhamnosus. Capsules were obtained by extrusion method using CaCl 2 as cross linker. An experimental design was performed using alginate and gelatin concentrations as the variables investigated, while the response variable was the concentration of viable cells. Beads were characterized in terms of size, morphology, scanning electron microscopy (SEM), moisture content, Fourier Transform In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(56 citation statements)
references
References 50 publications
4
49
0
3
Order By: Relevance
“…46 The peak intensity at $1639 cm À1 is characteristic of the -CONH 2 group, which indicated that the alginate's negative group is in all probability associated with gelatin's positive load. 47 Increased peak intensity at 1630 cm À1 , which corresponded to CONH 2 (C]O), could indicate that the alginate's negative group could be associated with gelatin's positive load. This observation is suggestive of intermolecular interactions between alginate and gelatin, which thus provide conclusive evidence of good molecular compatibility between the two polymers, which will improve its mechanical properties.…”
Section: Resultsmentioning
confidence: 99%
“…46 The peak intensity at $1639 cm À1 is characteristic of the -CONH 2 group, which indicated that the alginate's negative group is in all probability associated with gelatin's positive load. 47 Increased peak intensity at 1630 cm À1 , which corresponded to CONH 2 (C]O), could indicate that the alginate's negative group could be associated with gelatin's positive load. This observation is suggestive of intermolecular interactions between alginate and gelatin, which thus provide conclusive evidence of good molecular compatibility between the two polymers, which will improve its mechanical properties.…”
Section: Resultsmentioning
confidence: 99%
“…Besides, bands at 920 cm -1 and 822 cm -1 are attributed to the C-H vibration of the pyranose (ring of the alginate) group [23]. Compared with the spectrum of NaAlg beads and NaAlg treated with CNT/TiO 2 (1:b,c,d), the strong band of NaAlg beads at 1603 cm -1 which assigned to the carboxyl group shifted from 1608 cm -1 to 1627 cm -1 respectively indicating the specified intermolecular hydrogen bonds between the carboxyl group of NaAlg and CNT/TiO 2 [24]. The band at around 1704 cm -1 corresponding to the stretching mode of the carboxylic acid groups of the CNT [25], which is observed at the concentration of 10% of CNT/TiO 2 .…”
Section: Ftir Analysismentioning
confidence: 97%
“…The emulsified microcapsules contain a small particle size and do not affect the taste of the products in which the microcapsules are added. In addition, emulsification is more suitable for large-scale production [ 149 ].…”
Section: Applications Of Alginate In the Medical Fieldmentioning
confidence: 99%